Struggling for space and finding my place: An interactionist perspective on everyday use of biomedical information. (15th May 2014) - Wolf, Christine T.; Veinot, Tiffany C.
<x xml:space="preserve">Abstract</x> Information use intrigues information behavior researchers, though many have struggled with how to conceptualize and study this phenomenon. Some work suggests that information may have social uses, hinting that information use is more complicated than previous frameworks suggest. Therefore, we use a micro‐sociological, symbolic interactionist approach to examine the use of one type of information—biomedical information—in the everyday life interactions of chronic illness patients and their families. Based on a grounded theory analysis of 60 semi‐structured interviews (30 individual patient interviews and 30 family group interviews) and observations within the family group interviews, we identify 4 categories of information use: (a) knowing my body; (b) mapping the social terrain; (c) asserting autonomy; and (d) puffing myself up. Extending previous research, the findings demonstrate use of biomedical information in interactions that construct a valued self for the patient: a person who holds authority, and who is unique and cared for. In so doing, we contribute novel insights regarding the use of information to manage social emotions such as shame, and to construct embodied knowledge that is mobilized in action to address disease‐related challenges. We thus offer an expanded conceptualization of information use that provides new directions for research and practice.